THE ON-SCREEN ENVIRONMENT AND REALITY. THE PROBLEM OF RENDERING OF THE AUTHOR’S CONCEPT / ЭКРАННАЯ СРЕДА И РЕАЛЬНОСТЬ. ПРОБЛЕМАТИКА ТРАНСЛЯЦИИ АВТОРСКОЙ КОНЦЕПЦИИ - BAZANOV P.S. / БАЗАНОВ Ф.С. (Наука телевидения)
«Screen Projecting», rapidly spreading in various spheres of activities, is an integral part of screen culture of the XXI century. In most cases, the transition onto the screen plane is rather the requirement of the accelerated life pace. We are talking about three types of «visual projecting»: the creation of the screen object, existing after its release; simulated on the screen, the project is implemented in real space; self-contained screen model of an already existing real object.